The effect of letrozole vs clomiphene citrate for ovulation induction in patients of infertility with polycystic ovarian syndrome - Basarakod, Santosh S.; Bharadwaj, Meenakshi; V., Pruthvi Raj; N., Chaitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The overall prevalence of primary infertility in India is 3.9% to 16.8%. PCOS being a recognized cause of infertility, affects 8 to 13% of all reproductive-age women. Clomiphene citrate (CC) is most commonly used as first line drug for ovulation induction. CC is selective estrogen receptor modulator (SERM) and has adverse effect on cervical mucus and endometrial receptivity resulting in low pregnancy rates. Letrozole an aromatase inhibitor is considered as better alternative drug due to its benefits over CC. Thus, the aim of the present study is to assess the effect of letrozole and clomiphene citrate for ovulation induction in women with PCOS and compare the pregnancy rates. Methods: This is a hospital based randomized controlled study conducted on 89 patients at Armed forces medical college in western Maharashtra from June 2019 to May 22. Women with infertility due to PCOS attending OPD/IPD who fulfilled the inclusion criteria were included in the study. The subjects were divided into two groups through computer generated randomization and Group A of 45 subjects received letrozole for ovulation induction while Group B with 44 subjects received clomiphene citrate (CC). Data was analyzed and comparison among the study groups was done with the help of unpaired t test or Mann-Whitney test. Results: The number of mature follicles after treatment was significantly greater in clomiphene citrate group (1.59 ± 1.04) as compared to letrozole (1.02 ± 0.76). However, there was statistically significant greater mono ovulation with letrozole (55.2% vs 40.3%, p=0.03). After ovulation induction, the mean endometrial thickness was significantly greater in letrozole group as compared to CC (9.85±2.32 mm vs. 8.45±1.53 mm; p<0.05). Ovulation rate with letrozole was 42.5% vs 32.5% and pregnancy rate was letrozole 20% vs CC 7.5% which was statistically significant (p<0.05). Conclusions: Letrozole is a better drug for ovulation induction in women with PCOS with an ovulatory cycles as pregnancy rates are higher and lesser chance of multiple pregnancy.